Ventilation and Expansion of Intermediate and Deep Waters in the Southeast Pacific During the Last Termination. Issue 7 (2nd July 2020) - Haddam, N. A.; Michel, E.; Siani, G.; Licari, L.; Dewilde, F.
Abstract: We investigate the geometry and ventilation of the water masses within bathyal depths (~1, 500 to ~2, 500 m) of the Southeast Pacific (SEP), inferring the lower depth limit variations of the Antarctic Intermediate Water (AAIW) since ~22 kyr cal. BP. We use three cores collected at the upper limit of the Pacific deep waters, between 41°S and 49°S, and one core at a greater depth within this same water mass, at 46°S. The benthic foraminiferal assemblages and carbon and oxygen isotopes are used to show strong linkages between the timing of the deglacial Southern Ocean upwelling events and changes in the vertical extension and ventilation of the AAIW. In accordance with local/sublocal oxygen reconstructions, we propose at least three states of ventilation‐AAIW vertical extension: (i) the late glacial and the Antarctic Cold Reversal (ACR): AAIW depth‐limit shoals, as its formation zone moves northward; (ii) the deglaciation (excluding the ACR): the [O2 ] enrichment of the AAIW and the dominance of benthic species Trifarina angulosa indicate ventilated AAIW, along with a deepening of its lower limit; and (iii) the Holocene: enhanced influence of the Pacific deep water at bathyal depths (1, 500–2, 500 m) in the SEP north of ~46°S and the circumpolar deep water south of ~46°S. Key Points: We reconstructed the AAIW and PDW ventilation and geometry using δ13C, δ18O, and benthic foraminifera assemblages We observe a deepening of the AAIW during SO upwelling events during Termination I This deepening is probably accompanied by a southern extension of the AAIW